Genetic and non-genetic factors in prediction of early pubertal development in Chinese girls - Li, Weiqin; Du, Yuexin; Feng, Lingyan; Song, Panpan; Wang, Leishen; Zhang, Shuang; Li, Wei; Zhu, Dandan; Liu, Huikun (Frontiers in Endocrinology, 2024)
Objective: The objective of this study is to develop a combined predictive model for early pubertal development (EPD) in girls based on both non-genetic and genetic factors. Methods: The case-control study encompassed 147 girls diagnosed with EPD and 256 girls who exhibited normal pubertal development. The non-genetic risk score (NGRS) was calculated from 6 biochemical predictors of independent risk that screened by multifactorial logistic regressions, and the genetic risk score (GRS) was constructed using 28 EPD related single-nucleotide polymorphisms (SNPs). Area under receiver operator characteristic curve (AROC), net reclassification optimization index (NRI) and integration differentiation index (IDI) were used to evaluate the improvement of adding genetic variants to the non-genetic risk model. Results: Overweight (OR=2.74), longer electronic screen time (OR=1.79) and higher ratio of plastic bottled water (OR=1.01) were potential risk factors, and longer exercise time (OR=0.51) and longer day sleeping time (OR=0.97) were protective factors for EPD, and the AROC of NGRS model was 83.6% (79.3-87.9%). The GRS showed a significant association with EPD (OR=1.90), and the AROC of GRS model was 65.3% (59.7-70.8%). After adding GRS to the NGRS model, the AROC significantly increased to 85.7% (81.7-89.6%) (P=0.020), and the reclassification significantly improved, with NRI of 8.19% (P= 0.023) and IDI of 4.22% (P <0.001). Conclusions: We established a combined prediction model of EPD in girls. Adding genetic variants to the non-genetic risk model brought modest improvement. However, the non-genetic factors such as overweight and living habits have higher predictive utility.